MATHEMATICAL MODEL OF PHYTOHORMONE REGULATION OF ROOT MERISTEMATIC ZONE FORMATION - V. V. Lavrekha; N. A. Omelyanchuk; V. V. Mironova (Вавиловский журнал генетики и селекции)
The apical meristem located at the root tip of a plant is one of the most convenient objects to study the organization of the stem cell niche. In the root apical meristem, mitotically inactive cells of the quiescent center coexist with intensely dividing cells, which lose this ability at a certain distance from the quiescent center. It is known that plant hormones auxin and cytokinin play an important role in the regulation of this structure formation, but the mechanisms maintaining the dynamics of this structure remain unknown. We propose a mathematical model that summarizes experimental data on the distribution of auxin and cytokinin along the root longitudinal axis and their role in cell cycle regulation.